(untitled) (Wallingford, Oxfordshire, 2011)
Fully updated with new chapters linking strategic thinking and action in the management of tourism, this comprehensive textbook provides an analytical evaluation of the most important global trends in tourism and analysis of the impact of crucial environmental issues and their implications and the major factors affecting international tourism management. Following a successful first edition that is now a mainstream textbook in tourism courses, the book also covers marketing strategy, functional management and strategic planning in order to provide an integrated synthesis that will benefit students in their future careers, and also be useful to professionals working in the tourism sector.
Keywords: Tourism,Du lịch; Management,Quản lý